Un piccolo esempio. La psicagogia matematica di Platone - Marongiu, Laura (Brill, 2025)
‘Let me give you a simple example of what I mean, and you will see the rest for yourself.’ This is how Plato usually introduces mathematical examples to illustrate important philosophical puzzles. The research presented in this book offers a systematic analysis of these examples and demonstrates their crucial psychagogical function. Providing a toolkit of paradoxical objects that challenge the soul and summon thought, mathematical examples do not convey demonstrative rigor or exact calculations, but instead induce psychic states of aporia and wonder. The gaze of Plato’s mathematicians is directed both downwards and upwards: precisely for this reason mathematics have the power to awaken the soul and to lead it towards the Forms. «Prendi un piccolo esempio, e saprai tutto quello che voglio dire». Così Platone introduce esempi matematici volti a illustrare snodi filosofici particolarmente problematici. Questo studio fornisce un’analisi sistematica di tali esempi e ne mostra la cruciale funzione psicagogica. Come un toolkit di oggetti paradossali che confondono l’anima e mettono in moto il pensiero, le matematiche degli esempi non veicolano rigore dimostrativo e calcoli esatti, ma inducono stati psichici di aporia e meraviglia. Proprio in virtù del loro sguardo biforcuto, rivolto non solo verso l’alto ma anche verso il basso, le matematiche hanno il potere di risvegliare l’anima e di trainarla verso le Idee.